Reflections of Russian dialect geography in Djorža Karelian - Kehayov, Petar; Kuzmin, Denis; Blokland, Rogier (Suomalais-Ugrilaisen Seuran Aikakauskirja, 2021)
Can we place an Eastern Finnic dialect on the map, based exclusively on the Russian influence on its phonology and grammar? How precisely do differences between Russian (sub-)dialects manifest themselves in Eastern Finnic? Due to its unique location, far from its relatives, and its contacts with different Russian dialects, Djorža Karelian is a promising tool for answering these questions. We explore the distribution of three phonological features in Djorža Karelian vocabulary borrowed from Russian; all of them correspond to isoglosses on the Russian dialect map. In addition, we also briefly examine one syntactic feature in this Karelian variety: the distribution of two borrowed conjunctions with similar meaning and a North–South divide in Russian dialects. We conclude that phonology is not the best detector of contact between dialects of non-cognate languages, because of the relatively small sound inventory of the contact languages and the problems in distinguishing externally driven change from internally driven change. Syntax seems to be a better diagnostic for such contact, because of its complex relationship with meaning. We go on to demonstrate how syntactic evidence from a non-Slavic variety can be suggestive for the occurrence of linguistic phenomena in Russian dialects.